Why politicize the cultural game? (Emil) Cioran’s ethos: mysticism, religion and ethnic philosophy - Nicolau, Felix (Swedish Journal of Romanian Studies, 2024)
The present research aims at understanding some of Emil Cioran's spiritual positions in several of his writings. The tools of analysis are the philosophical and cultural approaches, but also elements of positivist determinism, such as climate, disease, etc. The oeuvres studied belong to different periods of creation. The working hypothesis is that the essayist remained a lifelong thinker oscillating between the extreme right and the extreme left, as well as a stubborn and metaphysically rejected progressive thinker, but always obsessed with metaphysics and the transcendent. Among the commonplaces of Cioran's artistic and geopolitical critique of reality and the real are narcissism, humor, victimhood and diatribe. His work is underpinned by intuition and Utopian projection and much less by logic. Cioran becomes dangerous if treated as a programmatic philosopher, but otherwise he is a spectacular source of artistic and literary-philosophical insights; an experimental essayist, dangerous as an influencer. The fate of his thinking has been heavily marked by the ideologies of his interpreters.